2014
DOI: 10.4049/jimmunol.1400571
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Activators of ERK5 Transcriptional Activity by High-Throughput Screening and the Role of Endothelial ERK5 in Vasoprotective Effects Induced by Statins and Antimalarial Agents

Abstract: Because extracellular signal-regulated kinase 5 (ERK5) inhibits endothelial inflammation and dysfunction, activating ERK5 might be a novel approach to protecting vascular endothelial cells (ECs) against various pathological conditions of the blood vessel. We have identified small molecules that protect ECs via ERK5 activation and determined their contribution to preventing cardiac allograft rejection. Using high throughput screening (HTS), we identified certain statins and anti-malarial agents including chloro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 49 publications
2
46
0
Order By: Relevance
“…Krüppel‐like transcription factors KLF2 and KLF4 are downstream targets for statin‐mediated ERK5 activation14; however, we detected no significant increase in KLF2 or KLF4 expression in RAW264.7 cells treated with anagliptin (data not shown), suggesting that the downstream effects of anagliptin‐mediated ERK5 activation in macrophages may be different from those of statins. Previous reports have indicated that ERK5 activation reduces cellular inflammatory responses by inhibiting the NF‐κB pathway 14, 32.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Krüppel‐like transcription factors KLF2 and KLF4 are downstream targets for statin‐mediated ERK5 activation14; however, we detected no significant increase in KLF2 or KLF4 expression in RAW264.7 cells treated with anagliptin (data not shown), suggesting that the downstream effects of anagliptin‐mediated ERK5 activation in macrophages may be different from those of statins. Previous reports have indicated that ERK5 activation reduces cellular inflammatory responses by inhibiting the NF‐κB pathway 14, 32.…”
Section: Discussionmentioning
confidence: 65%
“…Statins robustly activate ERK5 in endothelial cells, preventing endothelial dysfunction 14. In macrophages, ERK5 activation by statins enhances efferocytosis and plays a key role in atherosclerotic plaque formation in hyperlipidemic mice 15.…”
Section: Discussionmentioning
confidence: 99%
“…Sen-Banerjee et al show that statins enhance KLF2 promoter activity in human endothelial cells via monocyte enhancer factor binding sites and thus induce KLF2 expression [41]. This statin-mediated KLF2 up-regulation in endothelial cells depends on enhancement of ERK5 kinase activity [44]. Others show that statins can induce KLF2 expression in endothelial cells by regulating the apelin/APJ signaling pathway [45].…”
Section: Discussionmentioning
confidence: 99%
“…Activation of MEK5 and/or ERK5 per se leads to endothelial vasoprotection in both a KLF2-dependent and KLF2-independent manner, suggesting that additional targets of these kinases may be involved in mediating the beneficial effects of flow 181, 182 . One such target is the transcription factor Kruppel-like factor 4 (KLF4).…”
Section: Introduction and Overviewmentioning
confidence: 99%